Sustainable entrepreneurship out of entrepreneurial opportunity identification: The mediating role of psychological capital - Zhang, Hongxin; Chen, Hongxia (Frontiers in Psychology, 2023)
Introduction The aim of the present study, was to examine the simultaneous effects of entrepreneurial opportunity identification (EOI) and psychological capital (PC) on university students' entrepreneurial intention (EI). Compared with necessity-driven entrepreneurship, opportunity-driven entrepreneurship is more sustainable. Scholars have shown that EOI is key to forming EI, but little has been discussed about its association with PC. Methods A total of 555 university students in China were enrolled by means of convenience sampling. Descriptive statistics and correlation analysis of variables were performed using SPSS 21.0 software. Structural equation modeling analysis (SEM) with AMOS 21.0 was used to examine the structural effects of EOI and PC on university students' EI. Results According to the results, university students' EOI and PC had a positive and insignificant influence on their levels of EI. Furthermore, PC was found to fully mediate the impact of EOI on EI. Discussion The present study could shed light on new instructions to examine the interaction between the cognitive and psychological components of EI in the field of entrepreneurship. It is recommended that educators and practitioners should pay regard to the role of EOI and PC.